1996
DOI: 10.1016/s0736-5748(96)00049-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of developing substantia nigra in humans

Abstract: Electron microscopy of the maturing neurons and developing and maturing synapses in the substantia nigra of 14 human embryos/foetuses of 8-24 weeks of gestation are reported. At 8 weeks, cells were immature with very little cytoplasm and cellular organelles. Contact sites of processes appeared more electron dense than the other areas. At 12 weeks, many of the cells had acquired more cytoplasm and cellular organelles and could be identified as neurons. Asymmetric synapses with clear, round synaptic vesicles als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The cytoplasm contained distinct aggregates of short RER cisternae with many free polyribosomes between them and scattered mitochondria. The present results were in agreement with other studies [32,37] . Asymmetrical synapses with many synaptic vesicles and mitochondria were observed by electron examination of the SNc in this study.…”
Section: The Substantia Nigra Pars Compactasupporting
confidence: 94%
“…The cytoplasm contained distinct aggregates of short RER cisternae with many free polyribosomes between them and scattered mitochondria. The present results were in agreement with other studies [32,37] . Asymmetrical synapses with many synaptic vesicles and mitochondria were observed by electron examination of the SNc in this study.…”
Section: The Substantia Nigra Pars Compactasupporting
confidence: 94%
“…Postnatally, the number of synapses first continue to grow and later begin to decline until reaching stability in infancy or adulthood, depending on the brain region (Huttenlocher and de Courten, 1987; Huttenlocher and Dabholkar, 1997). It was demonstrated that in the human substantia nigra, synapses start to form by week 12 of gestation and become mature by week 15–16 (Sailaja and Gopinath, 1996). The synapse density reaches its peak in human auditory cortex by 3 months of age while in prefrontal cortex this occurs by 3.5 years of age.…”
Section: Synaptic Organization During Brain Developmentmentioning
confidence: 99%
“…Cytomorphological and molecular features of maturation of the nigral DA neurons are seeded during ontogenesis [21,22]. The total number of DA neurons at adulthood may thus be nalised during the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Preserved motor behavior and compensated/unaffected striatal local eld potentials in PD reminiscent conditions in CD-1 and the crossbreds complement the cytomolecular observations [18]. These features indicate that admixing imparts resilience.Cytomorphological and molecular features of maturation of the nigral DA neurons are seeded during ontogenesis [21,22]. The total number of DA neurons at adulthood may thus be nalised during the postnatal period.…”
mentioning
confidence: 99%